Development of Instructional Module Based on Inquiry-Interactive Demonstration to Improve Students’ Critical Thinking Skill - Itsna Yunida Al Husna; Mohammad Masykuri; Muzzazinah Muzzazinah (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
This research was a research and development (R&D) that produced products in the form of learning modules. The purpose of this research are to find out: (1) The characteristics of the material classification and its changes instructional module; (2) The feasibility of the material classification and its changes instructional module; (3) The instructional module effectiveness in increasing critical thinking skills. The procedure of this research are: (1) preliminary research & information gathering; (2) planning (3) initial product development; (4) initial field trial; (5) major product revisions; (6) main field test; (7) operational product revisions; (8) operational field test;(9) final product revision. The results of research and development show: (1) the characteristics of the instructional module as learning objects in accordance with the inquiry-interactive demonstration learning on the classification material and its changes; (2) instructional module eligibility based on experts assessment, education practitioners, and students produces 81.74% achievement with very good qualifications; (3) module as learning objects resulting from the development are effective in improving students' critical thinking skills with an N-Gain score of 0.561.